Enhancing Tourism Destination Competitiveness Through Digitalization - SWARI, Ni Luh Putu Intan Candra; FITRIANI, Ni Made; DEWI, Ni Putu Kesya Octika; SUNDARI, Ni Komang Rika (PT Batara Swastika Harati, 2025)
Digitalization has become a major driver in the transformation of the global tourism industry, especially in improving the competitiveness of destinations. This study aims to examine the role and contribution of digitalization to strengthening the tourism sector through a literature review study approach to 10 scientific journals published in the last five years (2021–2025). The results of the study show that digitalization has a significant impact on various aspects, such as destination marketing through digital media, the use of artificial intelligence in managing tourism content, the implementation of electronic payment systems, and the empowerment of tourism MSMEs. In addition, synergy between the government, business actors, and local communities is a key factor in optimizing the use of digital technology in an inclusive and sustainable manner. However, challenges such as infrastructure gaps, low digital literacy, and limited resources still need attention. Therefore, an adaptive and collaborative digitalization strategy is needed to encourage Indonesian tourism to be more competitive in the global market.